The genetics of virus particle shape in equine influenza A virus. (December 2013) - Elton, Debra; Bruce, Emily A.; Bryant, Neil; Wise, Helen M.; MacRae, Shona; Rash, Adam; Smith, Nikki; Turnbull, Matthew L.; Medcalf, Liz; Daly, Janet M.; Digard, Paul
Abstract : Background: Many human strains of influenza A virus produce highly pleomorphic virus particles that at the extremes can be approximated as either spheres of around 100 nm diameter or filaments of similar cross‐section but elongated to lengths of many microns. The role filamentous virions play in the virus life cycle remains enigmatic. Objectives/Methods: Here, we set out to define the morphology and genetics of virus particle shape in equine influenza A virus, using reverse genetics and microscopy of infected cells. Results and Conclusions: The majority of H3N8 strains tested were found to produce filamentous virions, as did the prototype H7N7 A/eq/Prague/56 strain. The exception was the prototype H3N8 isolate, A/eq/Miami/63. Reassortment of equine influenza virus M genes from filamentous and non‐filamentous strains into the non‐filamentous human virus A/PR/8/34 confirmed that segment 7 is a major determinant of particle shape. Sequence analysis identified three M1 amino acid polymorphisms plausibly associated with determining virion morphology, and the introduction of these changes into viruses confirmed the importance of two: S85N and N231D. However, while either change alone affected filament production, the greatest effect was seen when the polymorphisms were introduced in conjunction. Thus, influenza A viruses from equine hosts also produce filamentous virions, and the major genetic determinants are set by the M1 protein. However, the precise sequence determinants are different to those previously identified in human or porcine viruses.